Omega-3 PUFA of marine origin limit diet-induced obesity in mice by reducing cellularity of adipose tissue - Ruzickova, Jana; Rossmeisl, Martin; Prazak, Tomas; Flachs, Pavel; Sponarova, Jana; Veck, Marek; Tvrzicka, Eva; Bryhn, Morten; Kopecky, Jan (Lipids, 2004)
Omega-3 PUFA of marine origin reduce adiposity in animals fed a high-fat diet. Our aim was to learn whether EPA and DHA could limit development of obesity and reduce cellularity of adipose tissue and whether other dietary FA could influence the effect of EPA/DHA. Weight gain induced by composite high-fat diet in C57BL/6J mice was limited when the content of EPA/DHA was increased from 1 to 12% (wt/wt) of dietary lipids. Accumulation of adipose tissue was reduced, especially of the epididymal fat. Low ratio of EPA to DHA promoted the effect. A higher dose of EPA/DHA was required to reduce adiposity when admixed to diets that did not promote obesity, the semisynthetic high-fat diets rich in EFA, either alpha-linolenic acid (ALA, 18:3 n-3, the precursor of EPA and DHA) or linoleic (18:2 n-6) acid. Quantification of adipose tissue DNA revealed that except for the diet rich in ALA the reduction of epididymal fat was associated with 34-50% depression of tissue cellularity, similar to the 30% caloric restriction in the case of the high-fat composite diet. Changes in plasma markers and adipose gene expression indicated improvement of lipid and glucose metabolism due to EPA/DHA even in the context of the diet rich in ALA. Our results document augmentation of the antiadipogenic effect of EPA/DHA during development of obesity and suggest that EPA/DHA could reduce accumulation of body fat by limiting both hypertrophy and hyperplasia of fat cells. Increased dietary intake of EPA/DHA may be beneficial regardless of the ALA intake.
Keywords: dieta; tuková tkáň; myši; Diet; obezita; omega-3 mastné kyseliny; Animals; Fatty Acids, Unsaturated; Mice; nenasycené mastné kyseliny; Adipose Tissue; Obesity; Fatty Acids, Omega-3; zvířata